Pemberian Ganti Kerugian Tanah Kas Desa untuk Jalan Tol Solo Mantingan II: Problematika Pelaksanaannya - Rangga Agung Chrisnawati; Sri Kistiyah; Priyo Katon Prasetyo (Tunas Agraria, 2018)
Abstract: Land is the government's capital in carrying out various developments in the public interest. Regulation about the release of land acquisition objects besides individual land contributes to the constraints that become problematic in every land acquisition carried out by the government. This research that aims to find out the problematic compensation of village's treasure land in Masaran Subdistrict and the efforts carried out by the Land Acquisition Committee carried out with descriptive qualitative methods. The result of the research is based on the interview result, the researcher documentation at the research location. The problems faced are a) The difficulty of finding replacement land; b) the procedur of disposal village's treasure land; c) Human resources; and d) The rest of the compensation money. While the efforts are a) The Village Goverment active in finding replacement land; b) Active communication between related agencies and also with sellers of replacement land; c) Assistance in making and completing of filing files for village's treasure land disposal.Keywords: land acquisition, compensation, the village's treasure land Intisari: Tanah merupakan modal pemerintah dalam melaksanakan berbagai pembangunan untuk kepentingan umum. Pengaturan mengenai pelepasan objek pengadaan tanah selain tanah perseorangan menyumbangkan kendala yang menjadi problematika dalam setiap pengadaan tanah yang dilaksanakan pemerintah.. Penelitian yang bertujuan untuk mengetahui problematika ganti kerugian tanah kas desa di Kecamatan Masaran serta upaya yang dilaksanakan oleh Panitia Pelaksana Pengadaan Tanah ini dilaksanakan dengan metode kualitatif deskriptif. Hasil penelitian disusun berdasarkan hasil wawancara, dokumentasi. Problematika yang dihadapi adalah a) Kesulitan mencari tanah pengganti; b) Prosedur pelepasan tanah kas desa; c) Sumber daya manusia; dan d) Sisa uang ganti kerugian. Sedangkan upaya yang dilaksanakan adalah a) Desa aktif dalam mencari tanah pengganti dengan memberi pengumuman dan komunikasi dengan warga; b) Komunikasi aktif antar instansi yang terkait dan antara desa dengan penjual calon tanah pengganti; c) Pendampingan dalam membuat dan melengkapi berkas-berkas pengajuan pelepasan tanah kas desa.Kata Kunci: pengadaan tanah, ganti rugi, tanah kas desa